Synthesis of Chalcone Derivatives by Phthalhydrazide-Functionalized TiO2-Coated Nano-Fe3O4 as a New Heterogeneous Catalyst - Nia, Forough M.; Farahi, Mahnaz; Karami, Bahador; Keshavarz, Raziyeh (Letters in Organic Chemistry, 2021)
Phthalhydrazide immobilized on TiO2-coated nano Fe3O4 (Fe3O4-P) was synthesized and characterized by FT-IR, XRD, SEM, EDS and VSM analysis. The resulting magnetic nanocatalyst was used as a catalyst for the synthesis of chalcone derivatives which affords the desired products in good to excellent yields. This catalyst can be isolated readily after completion of the reaction by an external magnetite field and reused several times without significant loss of activity.
Keywords: Claisen-Schmidt reaction